Islamic Minimarket Index based on Maqashid - Ismail, Ja'far; Nugraha, Akmal; Haiqal, Arrayan; Putra, Brilliant (Maqasid al-Shariah Review, 2023)
This research explores the concept and implementation of Islamic minimarkets as a retail business model run in accordance with the principles of Islamic economics. The main focus of this research is to understand the extent to which Islamic minimarkets integrate Islamic moral, ethical and economic principles into their daily operations. Through an in-depth analysis of shariah compliance, product innovation, and social impact, this research aims to provide better insights into the potential and challenges in the development of Islamic convenience stores in the modern retail ecosystem. It is hoped that the results of this study will contribute to our understanding of the incorporation of sharia principles in retail businesses as well as provide guidance for business owners and stakeholders to develop and support Islamic convenience stores as a sustainable and ethical alternative in today's market economy.